The Application Of Google Sites In Student Learning Outcomes At Sman 09 Bengkulu Selatan - Agustina , Esi; Asnawati, Asnawati; Fitria, Yenni (Jurnal Komputer Indonesia, 2024)
This research aims to explain the application of Google Sites in learning outcomes in the Informatics subject in learning outcomes for the integration of Ms-Word office applications in class XA students at SMAN 9 Bengkulu Selatan. The approach method used in the research is a qualitative descriptive method. The focus of the research carried out was to explain the application of Google Sites in learning outcomes in Informatics subjects. The results of the research were validation of material experts in the feasible category with an average assessment of 3.22 and validation of media experts in the Very Appropriate category with an average assessment of 3.52. The results of observations regarding the implementation of Google Sites obtained a percentage of Very Good at 19%, Good at 56%, Fairly Good at 13%, Poor at 2% and Very Poor at 2%. The results of the student questionnaire regarding the implementation of Google Sites obtained results in the Strongly Agree category of 25%, the Agree category of 70%, the Disagree category of 6% and the Strongly Disagree category of 0%. Based on these results, it can be concluded that the application of Google Sites in learning outcomes in the Informatics subject in the MS-Word office application integration learning outcomes of class XA students at SMAN 9 South Bengkulu is included in the good category.